Práticas pedagógicas nas aulas de matemática: um estudo exploratório nas escolas Xacriabá - Augusta Aparecida Neves de Mendonca (2007)
In this study I made an attempt to analyze and to describe the pedagogical practices of indigenous teachers who teaches Mathematics in Xacriaba schools, by focusing on the relation between school and the ethnic group routine, on the forms of participation that take place during the lessons and on the pedagogical choices performed by the teachers. The methodology builds on an ethnographic approach oriented by cultural theories having micro ethnographic aspects as a feature. The main procedures of data collection are classroom observations of three teachers in two distinct Xacriabá schools, interviews and the analysis of personal and official documents. The questions that emerged during the research were analyzed from the perspective of school ethnography inquiries, in special, from those of studies referring to school cultures articulated with the theories about culture, which are all through this current work. Other than those, I am also being supported by the studies concerning Brazilian mathematics education movements, Ethnomathematics and the actual Mathematics in the indigenous school education. At first, my reading of the current pedagogical practices in Mathematics lessons at Xacriabá schools indicates some features, which unfold not only patterns but also singularities related to the school time organization and to the tacit consent of a diversity of attendance to the school classroom. This study attempts so far to argue that the teachers´ pedagogical practices in Mathematics lessons are allied by different forms of participation, and also by the power relationship between the academic mathematical knowledge and the local mathematical knowledge. They reveal the configurations that are shaping the Mathematics in Xacriabá schools, here referred as Indigenous School Mathematics. Further, the teachers teaching styles point out the currently Indigenous school state of affairs; in special those of Xacriabá schools, where the teachers, having the text book as basis, learn to teach Mathematical material which they were never taught.